Asymptotics of Solutions of an Infinite System of Linear Algebraic Equations in Potential Theory - Gomilko, A. M.; Koval'chuk, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For bounded solutions x k of an infinite system of linear algebraic equations arising in potential theory in the course of investigation of an axially symmetric problem in the exterior of two spheres with equal radii, we obtain asymptotic formulas with respect to a parameter that characterizes the approach of the spheres to one another and for k → ∞.